The Utility of Efavirenz-based Prophylaxis Against HIV Infection. A Systems Pharmacological Analysis - Duwal, Sulav; Seeler, Daniel; Dickinson, Laura; Khoo, Saye; von Kleist, Max (Frontiers in Pharmacology, 2019)
Pre-exposure prophylaxis (PrEP) is considered one of the five `pillars' by UNAIDS to reduce HIV transmission. Moreover, it is a tool for female self-protection against HIV, making it highly relevant to sub-Saharan regions, where women have the highest infection burden. To date, Truvada is the only medication for PrEP. However, the cost of Truvada limits its uptake in resource-constrained countries. Similarly, several currently investigated, patent-protected compounds may be unaffordable in these regions. We set out to explore the potential of the patent-expired antiviral efavirenz (EFV) as a cost-efficient PrEP alternative. A population pharmacokinetic model utilising data from the ENCORE1 study was devel-oped. The model was refined for metabolic auto-induction. We then explored EFV cellular uptake mechanisms, finding that it is largely determined by plasma protein binding. Next, we predicted the prophylactic efficacy of various EFV dosing schemes after exposure to HIV using a stochastic simulation framework. We predicted that plasma concentrations of 11, 36, 1287 and 1486ng/mL prevent 90% sex-ual transmissions with wild type and Y181C, K103N and G190S mutants, respectively. Trough concentrations achieved after 600mg once daily dosing (median: 2017ng/mL, 95% CI:445-9830) and after reduced dose (400mg) efavirenz (median: 1349ng/mL, 95% CI: 297-6553) provided complete protection against wild-type virus and the Y181C mutant, and me-dian trough concentrations provided about 90% protection against the K103N and G190S mutants. As reduced dose EFV has a lower toxicity profile, we predicted the reduction in HIV infection when 400mg EFV-PrEP was poorly adhered to, when it was taken `on demand' and as post-exposure prophylaxis (PEP). Once daily EFV-PrEP provided 99% protection against wild-type virus, if ≥50% of doses were taken. PrEP `on demand' provided complete protection against wild-type virus and prevented ≥81% infections in the mutants. PEP could prevent >98% infection with susceptible virus when initiated within 24 hours after virus exposure and continued for at least 9 days. We predict that 400mg oral EFV may provide superior protection against wild-type HIV. However, further studies are warranted to evaluate EFV as a cost-efficient alternative to Truvada. Predicted prophylactic concentrations may guide release kinetics of EFV long-acting formulations for clinical trial design.